Enhancing Teachers’ Scientific Publication Competence: Challenges, Strategies, and Future Perspectives - Martina Martina; Evi Juliyanti; Fatimah Zohra; Zulfikar Zulfikar; Eva Novita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Teachers are increasingly required to engage in scientific publication as part of their continuous professional development; however, their publication competence remains relatively low. This condition is influenced by limited academic writing skills, research competence, time constraints, and insufficient institutional support. This study aims to analyze the development of teachers’ scientific publication competence by identifying key challenges, effectiveness indicators, and relevant strategies. This study employed a qualitative approach, utilizing a systematic literature review (SLR) based on the PRISMA method, which involved 64 articles published between 2020 and 2025. The findings indicate that teachers’ publication competence is influenced by interconnected individual, institutional, and systemic factors forming a multidimensional ecosystem. This study proposes a multidimensional ecosystem-based conceptual model that is dynamic and non-linear. Improving publication competence requires an integrated approach that combines structured training, continuous mentoring, institutional support, and the strengthening of a research culture. This model offers a more contextual and strategic framework for teacher professional development.